Youth urban mobility behaviours in Tunisian Sahel - Ghédira, Aymen; El Kébir, Mehdi (TeMA - Journal of Land Use, Mobility and Environment, 2022)
In this paper, we analyze a 2019 survey data in order to gain a better understanding of the urban mobility behaviours of Tunisian young people aged from 15 to 29 years old, in the Tunisian Sahel region. For this study, we selected 739 participants, scattered over 40 delegations each with a different structure. We distinguish two age groups: from 15 to 19 years old (31.8%) and 20 to 29 (68.2%). The descriptive analysis was conducted on two spatial scales: The region named also the great Tunisian Sahel (scale 1) formed by three costal governorates (scale 2): Sousse, Monastir, and Mahdia. The variables analysis falls into two main categories: "daily trips volume coupled to the modal choice”, and “the trip trinomial”: Distance, Time, and Costs. Significant differences have been found in mobility practices, not only between social and spatial levels, but also between the youngest of 15-19 years old and those of 20-29 years old, thus emphasizing trends in travel habits as a function of age.